Factors Informing the Voting Behaviour of Teaching Staff of Egbeoba High School Ikole- Ekiti in 2018 Ekiti Gubernatorial Election - Ebirim, Samuel Iheanacho; Ogunleye, Matthew Adebayo (African Journal of Stability and Development (AJSD), 2022)
Since the return of democracy to Nigeria in 1999, politics in Ekiti State has been characterised by swings in political and electoral behaviour in support of the two rival political parties. This has made the political terrain of the state unpredictable in respect of voters’ attitude during elections. This study examines the factors that influenced voting behaviour of the electorates in 2018 governorship election in Ekiti State. It also examines the interplay between the campaign promises and voters’ participation during the election. The study further ascertains whether party identification and gratification have an overriding influence on voting pattern in the 2018 governorship election. Data was obtained from both primary and secondary sources. Focus Group Discussions were used to sample the opinion of a secondary school teaching staff who are residents in Ikole-Ekiti, Ekiti State. Primary data gathered were analysed, using content-analysis method. The study discovered that campaign promises increased voters’ turnout and stimulated voting behaviour while vote-buying increased voter turnout but changes voters’ choice. It was also discovered that militarisation of the election has a less significant role to play in voting patterns.This study recommends that vote-buying should be discouraged as it affects democracy by producing candidates that are not credible.